2003
DOI: 10.1080/13284200410001707453
|View full text |Cite
|
Sign up to set email alerts
|

Treatment options for improving wellbeing in dementia family caregivers: The case for psychoeducational interventions

Abstract: This paper provides an empirical and conceptual rationale for the relative advantages of psychoeducational programs versus support groups for caregivers of people with dementia. The need for interventions that improve the well being of caregivers is well documented. We reviewed studies that have directly compared support‐based and psychoeducational interventions. Two major strengths of psychoeducational interventions are their emphasis on training caregivers in a variety of cognitive and behavioral skills for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…For example, it appears possible that psychosocial interventions, which have been shown to effectively reduce depressive symptoms (Brodaty & Hadzi-Pavlovic, 1990;Mittelman, Roth, Coon, & Haley, 2004;Sörensen, Pinquart, & Duberstein, 2002) and burden (Mittelman, Roth, Haley, & Zarit, 2004;Sörensen et al, 2002) among dementia caregivers, may also serve to enhance caregiver health. Specifically, treatments that help caregivers better manage depressive symptoms and reaction to problem behaviors, including psychoeducational and multicomponent interventions (Depp et al, 2003;Mittelman, Roth, Coon et al, 2004;Pusey & Richards, 2001;Sörensen et al, 2002), may have a protective effect on caregiver cardiovascular functioning. However, these assumptions are still preliminary and should be tested empirically.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it appears possible that psychosocial interventions, which have been shown to effectively reduce depressive symptoms (Brodaty & Hadzi-Pavlovic, 1990;Mittelman, Roth, Coon, & Haley, 2004;Sörensen, Pinquart, & Duberstein, 2002) and burden (Mittelman, Roth, Haley, & Zarit, 2004;Sörensen et al, 2002) among dementia caregivers, may also serve to enhance caregiver health. Specifically, treatments that help caregivers better manage depressive symptoms and reaction to problem behaviors, including psychoeducational and multicomponent interventions (Depp et al, 2003;Mittelman, Roth, Coon et al, 2004;Pusey & Richards, 2001;Sörensen et al, 2002), may have a protective effect on caregiver cardiovascular functioning. However, these assumptions are still preliminary and should be tested empirically.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, pilot research indicated that this approach was at least modestly effective at reducing Hispanic/Latino American caregivers’ distress (Gallagher-Thompson, Arean, Rivera, & Thompson, 2001). In fact, psycho educational groups have a solid history of effective use with dementia caregivers (Castle, Wilkins, Heck, Tanzy, & Fahey, 1995; Gallagher-Thompson & DeVries, 1994; Labrecque, Peak, & Toseland, 1992, see recent review on this topic by Depp et al, 2003). Recent work by Gallagher-Thompson, Lovett, et al (2000) with over 200 caregivers found that improvement in use of adaptive coping skills, as well as decrease in symptoms of depression, was associated with participation in the skill building programs compared to the control condition.…”
Section: Racial Ethnic and Cultural Differences In Caregivingmentioning
confidence: 99%
“…In addition, pilot research indicated that this approach was at least modestly effective at reducing Hispanic/Latino American caregivers' distress (Gallagher-Thompson, Arean, Rivera, & Thompson, 2001). In fact, psychoeducational groups have a solid history of effective use with dementia caregivers (Castle, Wilkins, Heck, Tanzy, & Fahey, 1995;Gallagher-Thompson & DeVries, 1994;Labrecque, Peak, & Toseland, 1992, see recent review on this topic by Depp et al, 2003). Recent work by Gallagher- Thompson, Lovett, et al (2000) with over 200 caregivers found that improvement in use of adaptive coping skills, as well as decrease in symptoms of depression, was associated with participation in the skill building programs compared to the control condition.…”
Section: Hispanic/latino American Caregiversmentioning
confidence: 99%